2017
DOI: 10.1093/cercor/bhw417
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hippocampal Functional Connectivity During Episodic Memory Retrieval in Autism

Abstract: Increasing recent research has sought to understand the recollection impairments experienced by individuals with autism spectrum disorder (ASD). Here, we tested whether these memory deficits reflect a reduction in the probability of retrieval success or in the precision of memory representations. We also used functional magnetic resonance imaging (fMRI) to study the neural mechanisms underlying memory encoding and retrieval in ASD, focusing particularly on the functional connectivity of core episodic memory ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
137
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(156 citation statements)
references
References 97 publications
16
137
2
1
Order By: Relevance
“…The absence of hippocampal correlates of subsequent memory early on in encoding is particularly interesting in light of inconsistency in the literature. Although hippocampal encoding effects have often been reported (Spaniol et al, 2009;Kim, 2011), many individual studies have not found them (e.g., Sommer et al, 2005;Haskins et al, 2008;Cooper et al, 2017;Tibon et al, 2019). Although variability in hippocampal encoding effects might be attributed to differences in memory strength and trial selection (Henson, 2005), the current results suggest an additional possible explanation--namely, that such inconsistencies might be related to the duration of the encoding event used in fMRI analyses.…”
Section: Discussionmentioning
confidence: 54%
“…The absence of hippocampal correlates of subsequent memory early on in encoding is particularly interesting in light of inconsistency in the literature. Although hippocampal encoding effects have often been reported (Spaniol et al, 2009;Kim, 2011), many individual studies have not found them (e.g., Sommer et al, 2005;Haskins et al, 2008;Cooper et al, 2017;Tibon et al, 2019). Although variability in hippocampal encoding effects might be attributed to differences in memory strength and trial selection (Henson, 2005), the current results suggest an additional possible explanation--namely, that such inconsistencies might be related to the duration of the encoding event used in fMRI analyses.…”
Section: Discussionmentioning
confidence: 54%
“…With less information to base their judgments on, this could be related to difficulties distinguishing old and new items and increased false alarm (FA) rates [e.g., Gardiner, Bowler, & Grice, ]. Qualitative differences are also supported by recent neurophysiological evidence suggesting that both episodic and semantic memory are associated with atypical patterns of neural activity in ASD [Gaigg et al, ; Massand, Bowler, Mottron, Hosein, & Jemel, ; Massand & Bowler, ; Cooper et al, ]. These studies, however, also show that covert physiological indices exist that can index the memory atypicalities that characterize the disorder.…”
Section: Introductionmentioning
confidence: 59%
“…These brain regions were chosen because both have been implicated in NDDs, such as autism. Changes in connectivity have been reported in the hippocampus and the somatosensory cortex of patients with autism vs neurotypical controls . Changes in hippocampal volume, and reduced branching of CA1 hippocampal neurons have also been reported in brains of autism vs neurotypical controls .…”
Section: Resultsmentioning
confidence: 95%